A Novel Derivative of the Natural Product Danshensu Suppresses Inflammatory Responses to Alleviate Caerulein-Induced Acute Pancreatitis - Ren, Zhengnan; Li, Hongli; Zhang, Miaoying; Zhao, Yalei; Fang, Xin; Li, Xiu; Chen, Wei; Zhang, Hao; Wang, Yang; Pan, Li-Long; Sun, Jia (Frontiers in Immunology, 2018)
Acute pancreatitis (AP), a common abdominal inflammatory disorder, is characterized by premature intracellular activation of digestive proteases within pancreatic acini and a consecutive systemic inflammatory response. Although the mechanism remains to be fully understood, inflammation is the main cause of pancreatic damage in AP. A novel compound [4-(2-acetoxy-3-((R)-3-(benzylthio)-1-methoxy-1-oxopropan-2-ylamino)-3-oxopropyl)-1,2-phenylene diacetate (DSC)], derived from danshensu, exhibits anti-inflammatory and anti-apoptotic properties in vitro. However, its potential beneficial effect in AP has not been demonstrated. This study aimed to investigate the effects and underlying mechanisms of DSC in experimental AP in mice. We found that DSC suppressed inflammatory responses in AP by inhibiting the activation of nuclear factor-κB (NF-κB), signal transducer and activator of transcription 3 (STAT3) and nucleotide-binding domain leucine-rich repeat containing family, pyrin domain-containing 3 (NLRP3) inflammasome. Furthermore, treatment with DSC modulated the infiltration of neutrophils and the phenotypes of macrophages in mice induced with AP. Interestingly, we found that the expression of nuclear factor-erythroid 2 related factor 2 (Nrf2) and its regulated antioxidant enzyme heme oxygenase-1 (HO-1), which modulate inflammatory activities, was significantly increased in DSC-treated groups. Together, our findings demonstrate that DSC alleviates pancreatic inflammation and damage in AP by inhibiting the activation of NF-κB, STAT3 and NLRP3 inflammasome and modulating immune cell responses.